Pulses : an analysis of demand and supply India. 1951-1971/by Kusum Chopra and Guru Shri Swamy - "Chopra, Kusum" (New Delhi, 1975)
Pulses, the major protein component in the Indian diet, has been one of the neglected areas in Indian Agricultural Economics. The need for rectifying this position has become acute in recent years because of the steady fall in the output and availability per capita of pulses in recent years even though there has been some increase in the output of cereals. That is why one of the very first projects assigned by the Institute to its Agricultural Development and Rural Transformation Unit was a study of the demand and supply of pulses in India during the period 1951-1971; and it was entrusted to two members of the staff of the Unit namely Dr (Miss) Kusum Chopra (Fellow) and Mrs Gurushri Swamy (Research Associate). This publication is the result of their joint study.
Keywords: Agriculture Economic aspects